2006
DOI: 10.1152/japplphysiol.01600.2005
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy impairs diffusive oxygen transport in the lung of dogs

Abstract: The spleen acts as an erythrocyte reservoir in highly aerobic species such as the dog and horse. Sympathetic-mediated splenic contraction during exercise reversibly enhances convective O2 transport by increasing hematocrit, blood volume, and O2-carrying capacity. Based on theoretical interactions between erythrocytes and capillary membrane (Hsia CCW, Johnson RL Jr, and Shah D. J Appl Physiol 86: 1460-1467, 1999) and experimental findings in horses of a postsplenectomy reduction in peripheral O2-diffusing capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…During exercise more O 2 is required by the working skeletal muscles and thus a shift from the optimal physiological to the optimal Htc value for maximal endurance performance is observed. To cover their high O 2 demand during strenuous exercise, some terrestrial vertebrate species, such as horses and dogs, but not mice, release stored erythrocytes into the circulation by splenic contraction (26,27). This mechanism elevates the blood O 2 -carrying capacity during exercise within seconds.…”
Section: Discussionmentioning
confidence: 99%
“…During exercise more O 2 is required by the working skeletal muscles and thus a shift from the optimal physiological to the optimal Htc value for maximal endurance performance is observed. To cover their high O 2 demand during strenuous exercise, some terrestrial vertebrate species, such as horses and dogs, but not mice, release stored erythrocytes into the circulation by splenic contraction (26,27). This mechanism elevates the blood O 2 -carrying capacity during exercise within seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Horses, for example, show a 65-75% increase of haematocrit during exercise (Boucher & Connes, 2008;Catalini, Dottavio, & Rasia, 2007), and greyhounds present a substantial increase in reticulocyte count (Horvath et al, 2014). Further, it has been demonstrated that these responses to exercise are abolished by splenectomy, both in horses (Kunugiyama et al, 1997) and in dogs (Dane, Hsi, Wu, Hogg, Hogg et al, 2006;Hsia et al, 1985;Vatner et al, 1974).…”
Section: Findings In Animal Experimentsmentioning
confidence: 99%
“…The technique has been described extensively (6,20,29). Based on individual performance, measurements were obtained at three to five workloads of differing intensities.…”
Section: Animalsmentioning
confidence: 99%